Manajemen Kualitas Produk dengan Metode Six Sigma pada CV. Roti Berkah 313 Kabupaten Kuningan - Robi Awaluddin; Elita Shinta Sadiyah; Lili Karmela Fitriyani (Program Studi Agribisnis, Fakultas Pertanian, Universitas Singaperbangsa Karawang, 2022)
This study aims to control the level of product quality defects in CV. Roti Berkah 313. Companies engaged in food products. The production results are not always perfect and there are often defective or damaged products that exceed the tolerance limit. In that case, the company must improve quality by reducing the level of defects or damage by using the six sigma method with the DMAIC stage, namely, Define, Measure, Analyze, Improve and Control. The results of the study using the six sigma method can be seen the value of DPMO on CV. Roti Berkah 313 is 543666.67 with a Sigma value at the level of 3,203. The defects experienced by the company consist of 2 types of defects, namely, loose bread and burnt bread. Factors that cause these defects include tools and machines, people, raw materials and production processes. After knowing the root of the problem, a proposed improvement is made to the company to improve and reduce the defects that occur. That to control the level of product quality defects using the six sigma DMAIC method applied by CV. Roti Berkah 313.